Stereodynamic tetrahydrobiisoindole “NU-BIPHEP(O)”s: functionalization, rotational barriers and non-covalent interactions - Storch, Golo; Pallmann, Sebastian; Rominger, Frank; Trapp, Oliver (Beilstein Journal of Organic Chemistry, 2016)
Stereodynamic ligands offer intriguing possibilities in enantioselective catalysis. “NU-BIPHEPs” are a class of stereodynamic diphosphine ligands which are easily accessible via rhodium-catalyzed double [2 + 2 + 2] cycloadditions. This study explores the preparation of differently functionalized “NU-BIPHEP(O)” compounds, the characterization of non-covalent adduct formation and the quantification of enantiomerization barriers. In order to explore the possibilities of functionalization, we studied modifications of the ligand backbone, e.g., with 3,5-dichlorobenzoyl chloride. Diastereomeric adducts with Okamoto-type cellulose derivatives and on-column deracemization were realized on the basis of non-covalent interactions. Enantioselective dynamic HPLC (DHPLC) allowed for the determination of rotational barriers of ΔG‡298K = 92.2 ± 0.3 kJ mol−1 and 99.5 ± 0.1 kJ mol−1 underlining the stereodynamic properties of “NU-BIPHEPs” and “NU-BIPHEP(O)s”, respectively. These results make the preparation of tailor-made functionalized stereodynamic ligands possible and give an outline for possible applications in enantioselective catalysis.
Keywords: atropisomer; enantioselective DHPLC; ligand design; non-covalent interactions; Okamoto phases; phosphine ligand; stereodynamic ligands